Predictors of adherence to isoniazid preventive therapy among HIV positive adults in Addis Ababa, Ethiopia - Mindachew Mesele; Deribew Amare; Tessema Fasil; Biadgilign Sibhatu (BMC, 2011)
Abstract Background Isoniazide preventive therapy (IPT) is given to individuals with latent infection of tuberculosis (TB) to prevent the progression to active disease. One of the primary reasons for failure of IPT is poor adherence. Methods A cross sectional study was conducted in four hospitals in Addis Ababa. Data were collected using a pre-tested interviewer-administered structured questionnaire. Bivariate and multivariate analysis was done to identify predictors of IPT. Results A total of 319 (97.5%) individual participated in this study. Within seven days recall period, self-reported dose adherence rate was 86.5%. Individual who received explanation about IPT from health care providers (OR = 7.74; 95%CI: 3.144, 19.058); who had good feeling/comfortable to take IPT in front of other people [OR = 5.981, 95%CI (2.308, 15.502)] and who attended clinical appointment regularly (OR = 4.0; 95%CI: 1.062, 15.073) were more likely to adhere to IPT. Participants who developed IPT related adverse effect were 93% less likely to adhere to the prescribed doses (OR = 0.065; 95%CI: 0.024, 0.179). Conclusion The prevalence of self reported dose adherence over the past 7 days was higher. Non-adherence was observed among respondent who were not provided with sufficient information about IPT. The health care providers need to strengthen their educational and counseling efforts to convince the patient before putting them on IPT. To enhance adherence, health education efforts should focus on the importance of IPT, the details of the regimen and adverse effects.